1988
DOI: 10.1080/00288233.1988.10423437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Duroc in comparison with the Landrace and Large White as a terminal sire of crossbred pigs slaughtered at 85 kg liveweight

Abstract: A study was undertaken to evaluate the Duroc as a terminal sire in a three-way cross compared to a ~o-way backcross w~th the Landrace and Large WhIte breeds. It compnsed an analysis of litter records from seven farms and growth and carcass measurement data collected on three farms, along with the production ofDuroc and Landrace crossbreds at a central location and their comparative evaluation in three feeding trials. On the farms, Duroc-sired litters had relatively fewer stillbirths but breed of sire did not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…A major feature of using the Hampshire as a terminal sire in crossbreeding with the White breeds, which has been reported on numerous occasions (Smith et al 1988) is a marked improvement in the cross-sectional area of the "eye muscle" attributable primarily to a greater depth of lean tissue in the muscle, and this improvement was confirmed in the present study including the Duroc crossbreds. Support for the latter comes from overseas studies where Duroc crosses have generally not had larger "eye muscles" in cross-section compared with the White crosses (Simpson et al 1987)and from work conducted at this Centre which showed that a large eye muscle area is not a notable feature of the Duroc incomparison withtheLargeWhite (Smith& Pearson 1986) and the Landrace (Smith & Pearson 1987).…”
Section: ]~0supporting
confidence: 83%
See 2 more Smart Citations
“…A major feature of using the Hampshire as a terminal sire in crossbreeding with the White breeds, which has been reported on numerous occasions (Smith et al 1988) is a marked improvement in the cross-sectional area of the "eye muscle" attributable primarily to a greater depth of lean tissue in the muscle, and this improvement was confirmed in the present study including the Duroc crossbreds. Support for the latter comes from overseas studies where Duroc crosses have generally not had larger "eye muscles" in cross-section compared with the White crosses (Simpson et al 1987)and from work conducted at this Centre which showed that a large eye muscle area is not a notable feature of the Duroc incomparison withtheLargeWhite (Smith& Pearson 1986) and the Landrace (Smith & Pearson 1987).…”
Section: ]~0supporting
confidence: 83%
“…Of some significance in the present study was the relatively lower stillbirth rate in litters sired by Duroc and Hampshire boars compared with Large White and Landrace boars. This effect was observed previously when the Duroc in comparison with the Large White and Landrace breeds was the terminal sire in a crossbreeding study (Smith et al 1988).…”
Section: ]~0supporting
confidence: 77%
See 1 more Smart Citation
“…When interbreeding was used in the 3 rd and 4 th experimental groups, there was a tendency to an increase in the early maturity of young pigs by 3.6% and 2.9%, respectively, with a difference in relation to the 1 st control group. In the experiments carried out in [12], no significant differences were found between animals of the Landrace and Large White breeds, as well as between the offspring obtained as a result of crossing these breeds, according to the age of reaching a live weight of 85 kg by the time of slaughter (174, 175 and 172 days, respectively). Studies [13] in Northern Ireland did not prove the superiority of the Large White and Landrace hybrids over purebred peers in terms of average daily gain and feed conversion.…”
Section: Pig Fattening Qualitiesmentioning
confidence: 86%